2002
DOI: 10.1152/ajpendo.00173.2001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term high-fat feeding leads to severe insulin resistance but not diabetes in Wistar rats

Abstract: . Longterm high-fat feeding leads to severe insulin resistance but not diabetes in Wistar rats. Am J Physiol Endocrinol Metab 282: E1231-E1238, 2002. First published January 15, 2002 10.1152/ajpendo.00173.2001.-Although lipid excess can impair ␤-cell function in vitro, short-term high-fat feeding in normal rats produces insulin resistance but not hyperglycemia. This study examines the effect of long-term (10-mo) high polyunsaturated fat feeding on glucose tolerance in Wistar rats. The high fat-fed compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
78
3
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 45 publications
18
78
3
2
Order By: Relevance
“…This suggests that adipose tissue insulin resistance was specific with respect to glucose metabolism, but not to the control of lipolysis. Similar findings have been described in other studies [25,29,34]. This notion of selective insulin resistance has recently been described in liver [17,35].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that adipose tissue insulin resistance was specific with respect to glucose metabolism, but not to the control of lipolysis. Similar findings have been described in other studies [25,29,34]. This notion of selective insulin resistance has recently been described in liver [17,35].…”
Section: Discussionsupporting
confidence: 91%
“…Here, we show that whole-body insulin sensitivity does not deteriorate further beyond 3 weeks of HFD in mice, indicating that insulin resistance develops rapidly but reaches a plateau that is maintained over the course of further fat feeding. When comparing short-(3 week) [28] and long-term (10 months) [29] HFD protocols in rats, whole-body insulin sensitivity is reduced by ∼60% when compared with lean chow-fed controls, irrespective of how long the rats are maintained on the HFD. This supports the notion that insulin resistance has a limit that, once reached, is not exacerbated by further HFD and subsequent gains in adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in body fat was associated with higher levels of basal blood glucose and plasma leptin, a hormone signaling metabolic status from the adipocyte to peripheral tissues and the brain. There was no indication that high-fat feeding in our Long-Evans rats led to impaired glucose tolerance as previously found in Wistar and Sprague-Dawley rats, 20,21 in contrast to what others found in Wistar Imamichi rats. 21 Plasma insulin in response to high-fat diet has been shown to be either unchanged 21 or increased, 19,22 while a decrease was noted in the present study (Table 1).…”
Section: Induction Of Dietary Obesity and Circadian Desynchronizationcontrasting
confidence: 82%
“…This is reiterated in Wistar rats fed a high level of saturated fats. Although very long-term (10 months) high-saturated-fat feeding of Wistar rats leads to severe insulin resistance, overt diabetes does not develop [26]. In the highsaturated-fat feeding protocol of Wistar rats used in the present study (female Wistar rats; moderate lipid content; 4 weeks of dietary manipulation), euglycaemic-hyperinsulinaemic clamp studies have demonstrated peripheral insulin resistance, but unimpaired hepatic insulin sensitivity [11], and enhanced insulin secretion that allows maintenance of glucose tolerance [15].…”
Section: Discussionmentioning
confidence: 99%